Statistical approach of groundwater quality assessment at Almopia basin, Macedonia, North Greece. - Mattas, Christos; Veranis, Nikolaos; Soulios, Georgios; Kaklis, Triantafyllos (Bulletin of the Geological Society of Greece, 2020)
Groundwater quality is substantial for social and economic activities in Greece since the majority of the cultivated land is irrigated by water abstracted from aquifers, via a large number of wells and boreholes. The main sources of groundwater pollution are the fertilizers used in agriculture, and the disposal of untreated wastewater from domestic and industrial use. The plain part of Almopia basin, North Greece, is a rural area with intense agricultural activities (including livestock), without significant industrial activity or urban centers. Mild touristic activity has been developed during the last decades in the area of Loutraki, due to the exploitation of the local geothermal field (Pozar springs) for balneotherapy. The aim of this paper is to evaluate the groundwater quality using conventional statistical methods, as well as to employ multivariate statistical methods (factor analysis, cluster analysis) in order to identify the main hydrogeological processes or human activities that affect and determine the water character. The area was selected because of the extended cultivating activities that take place within its boundaries and the availability of adequate data. According to the results of the implemented research, the groundwater samples are of good quality, whereas the chemical composition is mainly formed by the interaction between the water and the geological formations.